Estratégias de desreplicação aplicadas ao estudo da planta Alternanthera brasiliana e dos fungos endofíticos associados - Trapp, Marília Almeida (Universidade Federal de São Carlos, 2011)
Alternanthera brasiliana is widely used by Brazilian people as a folk medicine for the treatment of numerous diseases. However, little is known about its chemical composition and the microorganisms that live in association with it. This work proposed the use of dereplication strategies to establish a correlation between chemical compounds present in the plant and the antibiotic activity associated with it. These strategies were also used for study endophytic micro-organisms associated with this plant, since the metabolites present in plant tissues are often result of interaction between plants and different factors present in their habitat, such as micro-organisms. 50 strains of endophytic micro-organisms associated to Alternanthera brasiliana were isolated. High-Throughput Screening strategies, which envolved analytical techniques as LC-PDA-MS, LC-PDA-MS/MS, LC-SPE-NMR and antibiosis assays allowed identification of antibiotic compounds present in the A. brasiliana stems. These compounds are member of oxylipins group, among which we highlight the 13-Z,E-KODE, 13-E,E-KODE, 9-E,Z-KODE and 9-E,EKODE. Furthermore, were identified some depsipeptides compounds produced by a strain of Fusarium fungus, isolated as endophyte of A. brasiliana. Beauvericin, which is one of these compounds , is known for its antibiotic and insecticide activities. This compound was also found in the plant extracts, suggesting that endophyte microorganism could play a role in producing antibiotic compounds inside plant tissues.
Studies towards the dereplication of antibiotic constituents in Alternanthera brasiliana and associated microorganisms
Keywords: Produtos naturais; Microorganismos endofíticos; Espectrometria de massas; Plantas medicinais; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA